Islamic Economics and MSME Empowerment: Fish Processing Strategies in South Lampung - Novitasari; Nursyamsi Hamza; Zuhal Azzamul A'la (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2025)
This study examines empowerment strategies for Micro, Small, and Medium Enterprises (MSMEs) in the fish processing sector at BOM Pier Kalianda, South Lampung, with a particular focus on their implications from an Islamic economic perspective. Despite the area’s substantial potential in fish processing, MSMEs face persistent challenges, including limited facilities, restricted access to training, and insufficient financing. Employing a descriptive qualitative design, this research collected primary data through interviews and direct observation with 23 informants, complemented by secondary sources from documents and literature. Data were analysed using the Importance Performance Analysis (IPA) method to assess the importance and satisfaction levels of 35 empowerment indicators. The findings show that product innovation training, access to raw materials, and financing fall under Quadrant II (priority for improvement), whereas local market access, product quality, and marketing training fall under Quadrant I (to be maintained). From an Islamic economic perspective, empowerment enhances distributive justice, promotes ethical business conduct, and fosters economic self-reliance among coastal communities. The results highlight that empowerment efforts at BOM Pier have generated positive impacts but remain constrained by technical skill gaps, limited access to Sharia-compliant financing, and weak compliance with quality standards. Strengthening policy coordination, infrastructure provision, and financing schemes rooted in Islamic principles is therefore essential for ensuring sustainable MSME development and inclusive economic growth.